Hydroponic Vegetable Production in Florida - Richard Tyson; Robert Hochmuth; Daniel J. Cantliffe (EDIS)
HS405, an 8-page illustrated fact sheet by Richard Tyson, Robert Hochmuth, and Daniel J. Cantliffe, provides an overview of hydroponic vegetable production in Florida — history, marketing considerations, growing systems, seasonal limitations, and economic considerations. Includes references. Published by the UF Department of Horticultural Sciences, November 2009.